PROSPEK DAN STRATEGI PENGEMBANGAN EKOWISATA MANGROVE DI KELURAHAN TERITIP BALIKPAPAN - Ningsy Indrianti Junus; H. Iwan Suyatna; A. Syafei Sidik (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2019)
The aim of the research are to describe prospect and  development strategy of mangrove ecoturism in Teritip, East Balikpapan and the potential of ecotourism  development in mangrove forest. Mangrove area at Sub distric Teritip, East Balikpapan was exploitation by local community such as conversion of mangrove forest to fishpond area, settlement,cutting of wood for firewood. The main objective of this research was to formulated strategy of sustainable mangrove ecoturism at Teritip. The result showed that the Mangrove Ecoturism Teritip has potential aspects to develop in reffering to the ecology place, the natural resources including flora and fauna